If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4x + -2) = -156 Reorder the terms: 6(-2 + 4x) = -156 (-2 * 6 + 4x * 6) = -156 (-12 + 24x) = -156 Solving -12 + 24x = -156 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 24x = -156 + 12 Combine like terms: -12 + 12 = 0 0 + 24x = -156 + 12 24x = -156 + 12 Combine like terms: -156 + 12 = -144 24x = -144 Divide each side by '24'. x = -6 Simplifying x = -6
| 7(3--4)-3(-2+2*3)= | | -23+3y=24+5y | | 15+0=15 | | 2w^2+w+66=0 | | 15z+4-17Z-8= | | -3+5x=17 | | 9x+16=169 | | x/3+4=10 | | 6=3/4(0)+b | | -6(-7+v)=66 | | x^3-15x^2+71x-103=0 | | 6x-9y=12 | | 71-5y=9x-13 | | 9z^2-3z+18= | | 4n-27=-20+3n | | 0.625(g-6)=-35 | | 91-2x=x | | 4(1.25c+6)-2c=-9 | | 1/2(3-x)-1/3(x+2)=3/4 | | x+(-10)=12 | | 6x-9y=12solvey | | 4(2-x)+2(1-5x)=5(2-3x)+x | | 6x^4-15x^6= | | 6x=7.20 | | 52-8= | | 9(n-15)-17n=-3-9(n+13) | | 21=-3p-6 | | b+9+2b=6 | | 3x+x-10=90 | | x-0.6=9.64 | | 3+12b+36a= | | 0-y=8 |